Pelatihan Manajemen Keuangan Keluarga Untuk Memperkuat Kesejahteraan Keluarga Anggota Credit Union Kasih Sejahtera Sedati - Dominicus Wahyu Pradana; Yulius Koesworo; Lena Ellitan; Ninuk Muljani (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2019)
This community service aims to reveal partners' problems by conducting surveys, interviews and discussions with cooperative management and management. The target family activities of the members of the CU Kasih Sejahtera cooperative. This activity is carried out in 2 stages. The first stage was on July 6, 2019 and the second stage was on July 7, 2019. The results of this activity were very satisfying, because many participants shared or discussed